2014
DOI: 10.1590/s0100-06832014000500022
|View full text |Cite
|
Sign up to set email alerts
|

Erosão hídrica pós-plantio em florestas de eucalipto na bacia do rio Paraná, no leste do Mato Grosso do Sul

Abstract: Nas regiões tropicais, o desgaste provocado no solo por ação das águas da chuva, ou seja, a erosão hídrica é a mais importante forma de degradação do solo. Visto que os plantios florestais de eucalipto estão inseridos em ecossistemas sensíveis às perturbações antrópicas em razão de ocorrência de plantações em solos com baixos teores de argila, com baixa fertilidade natural e grande parte das plantações estabelecidas em antigas áreas agrícolas e de pastagens degradadas, surge a necessidade do entendimento dos p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
1
6
0
11
Order By: Relevance
“…The tolerance values found corroborate values presented in the literature, from 9 to 11 Mg ha -1 yr -1 for Hapludox (Oliveira et al, 2011;Cândido et al, 2014). As the present study was conducted in the rainy season (crop season from November to March each year), which corresponds to approximately 75 % of total annual rainfall (Mello et al, 2007), it is possible that soil loss values of bare soil plots (7.42, 8.27, and 14.10 Mg ha -1 per period) exceed such soil loss tolerance limits when the whole year is considered.…”
Section: Rev Bras Cienc Solo 2018;42:e0170081supporting
confidence: 89%
“…The tolerance values found corroborate values presented in the literature, from 9 to 11 Mg ha -1 yr -1 for Hapludox (Oliveira et al, 2011;Cândido et al, 2014). As the present study was conducted in the rainy season (crop season from November to March each year), which corresponds to approximately 75 % of total annual rainfall (Mello et al, 2007), it is possible that soil loss values of bare soil plots (7.42, 8.27, and 14.10 Mg ha -1 per period) exceed such soil loss tolerance limits when the whole year is considered.…”
Section: Rev Bras Cienc Solo 2018;42:e0170081supporting
confidence: 89%
“…A predominância de agregados de tamanho silte no LVdf é particularmente preocupante, visto que seu diminuto tamanho facilita o transporte durante a enxurrada, conforme relatado por Cândido et al (2014). Além disso, ocupando posições elevadas tanto na encosta quanto no perfil, é facilmente removido e transportado encosta abaixo.…”
Section: Resultsunclassified
“…Essa concentração decorre do acúmulo de agregados maiores, enquanto os agregados de tamanho silte e a argila continuam a ser transportados até os cursos d'água. Estudo sobre erosão em Latossolo Vermelho distrófico textura média no Cerrado constatou a presença de maiores teores de areia do que argila na camada superior do solo na ocorrência de selamento superficial (Cândido et al, 2014). A maior percentagem de argila dispersa em todos os horizontes do GMbd demonstra menor atuação das forças de agregação/coesão no ambiente saturado em relação aos solos mais secos a montante.…”
Section: Resultsunclassified
“…A recent study carried out by Cândido et al (2014), which evaluated soil losses in homogeneous eucalyptus forest, showed the importance of adopting conservationist practices in slopes.…”
Section: Resultsmentioning
confidence: 99%